Criminal careers in transition : the social context of desistance from crime - Farrall, Stephen; Hunter, Ben (Lecturer in Criminology); Sharpe, Gilly; Calverley, Adam (Oxford : Oxford University Press, 2014)
This study follows the completion of a fifth sweep of interviews with members of a cohort of former probationers interviewed since the late 1990s. The research has been about developing a long-term evidence base, rather than a rapid assessment which does not have the time fully to explore the issue, namely whether (and how) probation supervision assists desistance from crime. The book explores how probation supervision helped people to stop offending, and investigates new areas (such as victimization, citizenship, emotional trajectories of reform, & the spatial dynamics of desistance).
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on September 3, 2014).
Keywords: Probation -- Great Britain -- Evaluation; Criminals -- Rehabilitation -- Great Britain; Recidivism -- Great Britain -- Prevention; Change (Psychology)